Strengthening professional expertise: mentoring in knowledge transfer, the cataloguers' perspective - Bello, M.A; Mansor, Yushiana (Elsevier Ltd, 2013)
University libraries provide support for institutions to achieve their objectives. To realise these objectives, universities allocate considerable funds for the library's development and provision of needed resources that support teaching/research activities. This is for the simple reason that a university's excellence is synonymous with the effectiveness of its library services. Hence, there is a need for continuous training and retraining for retention of librarians who manage the libraries to achieve the university's objectives. Of the few on-the-job training models, mentoring as a Continuing Professional Development programme for librarians in a university library has often been overlooked. This study surveys the uses of mentoring in knowledge transfer for cataloguing, managerial, and research skills development for cataloguers in Nigerian academic libraries. The findings show that mentoring as a tool for knowledge transfer influences cataloguers and their skills development. The result indicates that mentoring in knowledge transfer has a moderate to strong correlation with skills development, and it improves catalouers' proficiency and overall development.